Hawala e Daigou: riciclaggio di denaro e patto d’onore tra Nigeria e Cina - Massimo Bonino (Rivista di Criminologia, Vittimologia e Sicurezza)
This paper offers a brief examination of the money transfer method typically used in the African and Asian continents and in Islamic communities called hawāla whose constituent elements - tradition, trust and honor - make a credit instrument unique from a cultural perspective, even before a criminal one. The interesting fact is that the arsenal available to the police and the judicial authorities in the matter of combating money laundering could, however, prove almost inhibited in front of a mechanism so rudimentary as to be - paradoxically - much more efficient than more refined or technologically advanced money transfer systems.